Influence Structure Capital to Income on Low Voltage Electrical Inspection Company PT (Cilister) Field - Diwehati Salawajo; Hendry Hendry (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
Electricity is one of the most essential parts of life Which done by man Which where all equipment Which There is at home ladder need Power electricity. Study This uses type study descriptive quantitative. Type of Data collected in the study This uses primary data and secondary data. Technique Collection Interview data, Observation, study documentation. As for the results discussed in the research, based on the data above, the variable mean value income is 69,611,111 with a standard deviation of 7,156,526. In contrast, the mean variable Structure Capital is 36,194,444, with a standard deviation of 11,629,566. Equality regression compelled several conclusions: (1) Value constant that is 89891010 gives mark variable company without influence variable independent. (2) Coefficient regression (β)value as big-0.560 shows the influence of negative variable regarding capital structure, that is, inclined capital structure decreases when income increases.